Persepsi Pengunjung Terhadap Tingkat Kenyamanan Alun-Alun Kabupaten Pemalang - Galang Kahar Paningkat; Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Population growth rates and city development which is increasing drastically will increasingly improve urban services.Same time it will have a negative impact on the protection of nature so that in realizing a sustainable city, it is necessary to provide green open space as a counterweight to the environment. The form of green open space in urban areas is a parks. Pemalang Regency has a city park that is Pemalang Town Square. Public space meetings are a basic requirement. If there is no comfort in public spaces, it is difficult to see the needs of visitors in public spaces as users. the purpose of the study was to study the comfort level of Pemalang Town Square according to the perceptions of visitors. Visitors are taken as research objects because they are users of green open space, so their position is important as an evaluation of a planning program.The results of the study are the comfort level of Pemalang Town square based on the perceptions of visitors included in the convenient category. However, there are still aspects that still need to be improved to improve comfort such as lighting facilities in the park that are dim at night.